2015
DOI: 10.1016/j.diabet.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

A family history of diabetes determines poorer glycaemic control and younger age of diabetes onset in immigrants from the Middle East compared with native Swedes

Abstract: The study shows that the greater predisposition to diabetes in Middle Eastern immigrants may be explained by a more extensive family history of the disorder; clinical interventions tailored to Middle Eastern immigrants with such a family history are thus warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…We have concluded that the lower disposition index in the non-diabetic immigrant population can contribute to their higher HbA1c levels and earlier diabetes onset [9]. Here we show that BMI and waist circumference levels for the corresponding levels of disposition index are even lower than for the corresponding levels of insulin resistance reflecting that we do not overestimate the impact of BMI and waist circumference on diabetes risk in the Iraqi born population.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…We have concluded that the lower disposition index in the non-diabetic immigrant population can contribute to their higher HbA1c levels and earlier diabetes onset [9]. Here we show that BMI and waist circumference levels for the corresponding levels of disposition index are even lower than for the corresponding levels of insulin resistance reflecting that we do not overestimate the impact of BMI and waist circumference on diabetes risk in the Iraqi born population.…”
Section: Discussionmentioning
confidence: 46%
“…Dysfunctional insulin sensitivity, or insulin resistance, is dependent on ectopic fat accumulation in liver, visceral adipose tissue, and skeletal muscle [8]. Although the Iraqi immigrant population is generally more obese (BMI > 30 kg/m 2 ) than the native Swedish population (37.5% vs 23.0%, p  < 0.001) [9], the reduced insulin sensitivity in this population is not fully explained by BMI or other cardiometabolic risk factors [7]. These findings are consistent with other studies reporting different fat distributions across ethnicities and consequently highlight the limitation of BMI as a measure of adiposity [10].…”
Section: Introductionmentioning
confidence: 99%
“…Nordic studies of immigrants from countries where Kurds originate have examined the prevalence of T2DM or risk factors for the disease [14,15,[56][57][58][59][60][61]. A 2013 Swedish study confirmed, as expected, that the prevalence of T2DM was higher among Iraqi immigrants than Swedish participants (8.4% vs. 3.3%) [61].…”
Section: The T2dm Situation In Norwaymentioning
confidence: 79%
“…Our data further suggests that the Iraqi population with NAFLD is younger than the Swedish born population. This may reflect an earlier onset of disturbed fat metabolism contributing to insulin resistance and an earlier diabetes onset in Iraqi immigrants that we have previously reported [28]. Increased knowledge of the mechanisms triggering insulin action in different populations is important for better understanding in this high risk population for type 2 diabetes.…”
Section: Nafld and Ethnic Differencesmentioning
confidence: 60%